Keynote: The Landscape of Collective Management Schemes - Gervais, Daniel (The Columbia Journal of Law & the Arts, 2011)
The title for this address, suggested by Jane Ginsburg and June Besek, prompted me to take a fresh look at the rules of landscape composition. I found six major ones. The first five rules are as follows: (a) group your subjects of importance within a center of interest; (b) avoid straight lines; (c) allow the viewer to interact and become a participant; (d) make good use of contrast; and (e) add some drama and avoid kissing the edges. I can promise you two of those five, namely that we will interact later, and that I will not be kissing any edges this morning. Unfortunately, I cannot promise drama. As to the center of interest and avoidance of straight lines, let us see what we can do. The last rule is to put striking features in the foreground set against a solid background. That I think I can deliver. Let us start with the background. I will use a realist technique for this part of my talk.